Access to information in deaf and hard-of-hearing people - Eva Gutierrez-Sigut; Veronica Lamarche; Katherine Rowley; Emilio Ferreiro Lago; María Jesús Pardo-Guijarro; Ixone Saenz; Berta Frigola; Santiago Frigola; Delfina Aliaga; Laura Goldberg (PLoS ONE, 2026)
Deaf and Hard of Hearing (HoH) people often face communication barriers that limit their access to crucial information. This study investigates which modalities deaf people used to gather information from various sources, and which factors predicted accessibility, satisfaction, and wellbeing. We report the findings from an accessible survey study, released in two written and three signed languages. Responses from 395 deaf/HoH UK and Spanish residents were collected online shortly after the COVID-19 pandemic breakout. We investigated whether the onset and Level of Deafness, knowledge of sign language, Residence, and self-assessed reading skill predicted the frequency with which they found accessible information, their satisfaction levels with the information accessed, and their physical and mental health. We found that most deaf/HoH people relied on subtitles to access information from the government and the news, but when signed information was available (i.e., from deaf organisations), SL was the preferred modality of access. Our main finding was that reading skill was a key predictor, with less skilled readers being at a disadvantage, less satisfied, and having lower health outcomes. Our findings advocate for facilitating more signed information, as well as releasing written information at appropriate reading levels and improving literacy programmes for deaf people.